Zdravotně technické a plynovodní instalace v budově fotbalových šaten - Štefánek, Antonín (Vysoké učení technické v Brně. Fakulta stavební, 2018)
Bakalářská práce je zaměřena na řešení zdravotně technických a plynovodních instalací v budově fotbalových šaten. Teoretická část bakalářské práce se zaměřuje na problematiku hromadných hygienických zařízení. Ve výpočtové a projektové části se řeší rozvody kanalizace, vodovodu a plynovodu v zadaném objektu.

The bachelor thesis is focused on the solution of the sanitary and gas pipelines installations in the soccer building. The theoretical part of the bachelor thesis focuses on the issue of mass sanitary equipment. The sewerage, water supply and gas pipelines in the given building are solved in the calculation and design part.
Sanitation installation and gas installation in the football cloakroom building
Keywords: Hromadné hygienické zařízení; umývárny; záchody; pisoáry; zdravotně technické a plynovodní instalace; fotbalové šatny.; Mass sanitary equipment; washrooms; toilets; urinals; sanitary and gas pipelines installation; soccer dressing rooms.